PENGAWASAN PEMERINTAH TERHADAP EKSPLOITASI SUMBER DAYA AIR PERMUKAAN UNTUK KEPENTINGAN USAHA PENJUALAN AIR BERSIH DI DESA KEJI KABUPATEN SEMARANG - Ardhitya Eka Prasetya; Wiwik Widayati; Puji Astuti (Journal of Politic and Government Studies, 2015)
Abstract Semarang District is an area that has the potential of this highly abundant water. Potential Water Resources has strategic value to be developed as shown by the development of clean water sales efforts in Semarang Regency. Utilization large will bring greater implications. Starting from the reduced flow of water for irrigation needs and the needs of the surrounding community.            Control of government becomes mandatory, as mandated by Article 33 paragraph 3 of the 1945 "Earth and water and natural resources contained in it are controlled by the state and used for - the people's welfare". In order to guarantee the fulfillment of the needs of the general public. Controls were performed include preventive and repressive control. Preventive done with legislation governing the rights perijian water uptake.From the repressive done with surface water sampling site supervision. In the implementation of government control dihadapakan on monitoring the implementation of the issues that are not in accordance with prescribed standards and are not making appropriate water licensing / even not permitted.            Recommendations are expected in the future the government is able to supervise compliance with standards and orderly in checking. It takes communication, coordination and commitment from government, businesses and communities around the extraction of water that the water exploitation can be run properly and in accordance with applicable regulations.            Keywords:  Control, WaterExploitation, Semarang District, Surface Water